The case for the relevant university - Botman, HR (South African Journal of Higher Education, 2011)
Stellenbosch University has gone through a serious engagement with the topic of a pedagogy of hope. The engagement included the initial proposal of Paulo Friere, the South American educationist, bearing the imprints of the twentieth century and the new ways in which intellectuals are revisiting the critical pedagogy of hope for the twenty first century. There are serious differences between the two efforts. However, a relevant pedagogy must be contextually designed in a clear acknowledgement of the needs and fears of all people in such a context. South Africa has a long way to go and this article is a contribution to the search of a conceptual framework to reconsider the renewal of the educational system.